An inventory to measure quality of familiar life - Carrasco, Beatriz; Salazar, Diego; Merino, José Manuel (Revista Chilena de Salud Pública, 2004)
<!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–> The objective of this project was to construct an inventory for the measurement of quality of family life in a Chilean population. The "universe of knowledge" was defined as a set of theoretical proposals for the measurement of the quality of family life considered to be paradigmatic in this field. This set of contents was complemented by the results of a DELPHI pannel representing an appraisal of the local consensus on the measurement of the quality construct. In the first part of the study a set of descriptors was derived both from the chosen universe of knowledge and the local Delphi appraisal. This set was then transformed into a list of self-report inventory indicators, the construct validity of which was ensured by the consensus between the universe of knowledge and the local panel. The final form of the inventory includes scales and scores for each indicator.